THE RELATIONSHIP BETWEEN CAREER DECISION SELF EFFICACY AND SELF PERCEIVED EMPLOYABILITY ON VOCATIONAL STUDENT - Mahdi, Salsabilla Syaifa; Rani Armalita (Causalita, 2025)
The high unemployment rate among vocational graduates in West Sumatra indicates a lack of student readiness to enter the workforce, which is influenced by low employability and limited self-confidence in their own abilities..The method in this study is a correlational quantitative design using Pearson Product Moment analysis. Respondent totaled 372 vocational student in Padang State Polytechnics . Data collection was carried out using a scale adapted from Career Decision Self Efficacy Scale-Short Form (CDSE-SF) and Self-Perceived Employability Scale. Reliability on CDSE-SF scale is .845 and on the self perceived employability scale is .829 based on the result of the Pearson Product Moment correlation analysis, it shows that there is a significant positive correlation with a correlation coefficient (r) of .229 (sig. (p) of .000). The result of this study indicate that there is a positive relationship between career decision self efficacy and self perceived employability on vocational student. So, it can be concluded that the higher career decision self efficacy, the higher the self perceived employability on vocational student.